Tinjauan Yuridis Pejabat Pembuat Akta Tanah Yang Menerima Titipan Dana Hasil Transaksi Jual Beli - Rifanti, Nia Puspa (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2022)
This study aimed to analyze the act of accepting deposited funds by the Land Deed Making Officer (PPAT) from a legal perspective and its juridical consequences. This study used a statutory, conceptual, and case research approach. The type of research used was normative juridical with the descriptive analysis method and legal interpretation. The study results showed that receiving deposited funds carried out by PPAT related to the effects of buying and selling transactions are not legally regulated in the legislation. PPATs who receive deposited funds from clients must comply with the agreement and have an obligation to keep the funds appropriately. The legal consequences for Land Deed Making Officer who misused the deposited funds were subject to Article 372 of the Criminal Code for embezzlement and Article 378 of the Criminal Code for fraud with a maximum imprisonment of four years. Land Deed Making Officers who were proven to have committed violations should be responsible for their actions by being subject to administrative, civil, and criminal sanctions.